Asuhan Kebidanan Continuity of Care (COC) pada Ny. “A” Umur 33 Tahun G6P5A0 di Desa Kebun Janda Kab.Bobong - La Tanjo, Yunita; Hapsari Windayanti (Universitas Ngudi Waluyo, 2024)
Continuity of care (COC) midwifery care is continuous midwifery care provided to mothers and babies starting during pregnancy, childbirth, newborns, postpartum and family planning. COC midwifery care is one effort to reduce the maternal mortality rate (MMR) and infant mortality rate (IMR)). Based on the description above, the author monitored Mrs. A pregnant, postpartum, neonate and family planning at the Bobong Community Health Center. Because the Puskesmas has met midwifery care standards and has an MOU with educational institutions. So the author is interested in carrying out midwifery care entitled